Questing As an Alternative for Mass Tourism In Times of the Pandemic - Karina TESSAR (Communications of International Proceedings, 2021)
The covid-19 pandemic is having a major impact on the entire tourism industry. Activities of accommodation facilities were restricted, transportation was impeded, access to many tourist attractions, cultural and entertainment institutions and recreational and sports facilities was limited. While being locked in their homes, people suffer from a lack of movement and social interaction, which are essential to keeping health and mental balance. For many people travel became a luxury, not so much in terms of affordability, but for safety and compliance reasons. However, there are forms of tourism and recreation that can be successfully developed in the times of the pandemic, while maintaining a sanitary regime. These include outdoor games such as questing. The aim of this paper is to present the qualities of questing as the perfect solution to the different challenges of 21st century tourism. This type of the game is now gaining popularity in times of epidemiological crisis, even though it was implemented in Poland over a decade ago.
Keywords: questing; alternative tourism; individual tourism; pandemic